"Effect of the number of Grooves of the distance between the optical fiber using a Wavelength of the window (λ=850nm)'' (Journal of the College of Basic Education, 2022)
I`ve been studying the effect of the number of grooves incised on the distance between the optical fiber using a Wavelength of the window. Were calculated the vector dispersion angular, as well as calculated the interval between channels optical, as well as the number of grooves incised on the distance between the optical fiber (center to center) using the Wavelength of the window. The note change the number of grooves incised as a function of the distance between the optical fiber the greater the number of grooves incised, the less distance between the optical fiber .Also note that the distance between the optical fiber increases with the value of interval between channels optical in spite of proven angle glow (Blaze angle). We also note that the distance between the optical fiber increases with lens focal length and note that the value of vector dispersion angular remains constant does not change while we find that the value of interval between channels optical is inversely proportional on the number of grooves incised and therefore less than the distance between the optical fiber has reached the amount of space that between fiber optic (b=40.7704µm) by using grating have (20 grooves per mm) when a lens focal length (f=5×10 4µm). When using either grating have (1800 grooves per mm) we note that the distance between fiber optic (b=0.4506µm) when a lens focal length(f=5×10 4µm) while (b=81.5409µm) when using grating have (20 grooves per mm) using the lens focal length (f=10×10 4µm) but when you using grating have (1800 grooves per mm) we note that the distance between the optical fiber using the (b=0.9013µm) by using the same lens focal (f=10×10 4) µm